Barbell kinematics should not be used to estimate barbell and body system centre of mass power in the back squat - Lake, J.; Lauder, M.; Smith, N. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
This study compared measures of barbell-and-body system centre of mass (CM) power obtained by multiplying ground reaction force (GRF) by a) barbell velocity, b) CM velocity derived from 3D motion analysis, and c) CM velocity derived from GRF during back squat performance. Results showed that the barbell was displaced (13.4%; p<0.05) more than the CM at a velocity that was 16.1% (p<0.05) greater than the CM (both GRF and 3D derived), which resulted in the GRF by barbell velocity power been 18.7% (p<0.05) greater than the GRF by 3D derived CM power. These were underpinned by significant differences between the velocity of the barbell and the trunk, upper-leg, and lower-leg (p<0.05), demonstrating that a failure to consider the kinematics of body segments during back squat performance can lead to a significant overestimation of CM power.